2023
DOI: 10.1021/acs.est.2c06739
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorononanoic Acid Induces Neurotoxicity via Synaptogenesis Signaling in Zebrafish

Abstract: Perfluorononanoic acid (PFNA), commonly used as an alternative polyfluorinated compound (PFC) of perfluorooctanoic acid (PFOA), has been widely detected in the aquatic environment. Previous ecotoxicological and epidemiological results suggested that some neurobehavioral effects were associated with PFC exposure; however, the ecological impacts and underlying neurotoxicity mechanisms remain unclear, particularly in aquatic organisms during sensitive, early developmental stages. In this study, zebrafish embryos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 81 publications
1
11
0
Order By: Relevance
“…The neurotoxic effects on the GABAergic system are typically investigated in zebrafish by analysing the expression of genes associated with the GABAergic pathway, such as GABA synthesizers [ gad1b ( Cheng et al, 2020 ; Shi et al, 2022 ; Yu et al, 2022 ; Ding et al, 2023 ; Xiang et al, 2023 ) and gad2 ( Ding et al, 2023 )], receptors ( gabra1 ( Shi et al, 2022 ; Liu et al, 2023 ; Ding et al, 2023 ), gabra6a ( Atzei et al, 2021 ), gabra6b ( Liu et al, 2023 ), gabrb3 ( Luo et al, 2023 ), gabrg2 ( Ding et al, 2023 ; Xiang et al, 2023 )), and transporters ( gat1 ( Cheng et al, 2020 ; Ding et al, 2023 ; Xiang et al, 2023 ), gat3 , vgat ). For example, exposure to lead has been shown to increase gad1b and gad2 expression and modulate the expression of gabra1 , gabbr1a , gat1 , gat3 , vgat expression ( Wirbisky et al, 2014 ) ( Supplementary Table S2 ).…”
Section: Neurotransmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…The neurotoxic effects on the GABAergic system are typically investigated in zebrafish by analysing the expression of genes associated with the GABAergic pathway, such as GABA synthesizers [ gad1b ( Cheng et al, 2020 ; Shi et al, 2022 ; Yu et al, 2022 ; Ding et al, 2023 ; Xiang et al, 2023 ) and gad2 ( Ding et al, 2023 )], receptors ( gabra1 ( Shi et al, 2022 ; Liu et al, 2023 ; Ding et al, 2023 ), gabra6a ( Atzei et al, 2021 ), gabra6b ( Liu et al, 2023 ), gabrb3 ( Luo et al, 2023 ), gabrg2 ( Ding et al, 2023 ; Xiang et al, 2023 )), and transporters ( gat1 ( Cheng et al, 2020 ; Ding et al, 2023 ; Xiang et al, 2023 ), gat3 , vgat ). For example, exposure to lead has been shown to increase gad1b and gad2 expression and modulate the expression of gabra1 , gabbr1a , gat1 , gat3 , vgat expression ( Wirbisky et al, 2014 ) ( Supplementary Table S2 ).…”
Section: Neurotransmissionmentioning
confidence: 99%
“…The impact on the dopaminergic system can be investigated by analysing the morphology of dopaminergic neurons ( Cui et al, 2013 ; Yao et al, 2017 ; Jin et al, 2019a ; Wang et al, 2019 ), aided by the availability of zebrafish transgenic lines with GFP-labelled dopaminergic neurons. Analysis of dopamine levels ( Wang et al, 2015 ; Sheng et al, 2016 ; Soares et al, 2017 ; Wang et al, 2019 ; Han et al, 2021 ; Yang et al, 2022 ) and its metabolite, hydroxy-phenyl acetic acid, along with the expression of dopamine transporter ( dat ) genes ( Ji et al, 2021 ; Gyimah et al, 2022 ), dopamine receptors ( drd1b ( Li et al, 2019 ; Tran et al, 2021 ; Hong et al, 2022 ; Liu et al, 2023 ), drd2a ( Cao et al, 2019 ; Gyimah et al, 2022 ; Shi et al, 2022 ; Liu et al, 2023 ; Ding et al, 2023 ; Mahapatra et al, 2023 ; Torres-Ruiz et al, 2023 ; Xiang et al, 2023 ), drd2b [ Shi et al, 2022 ; Liu et al, 2023 ; Torres-Ruiz et al, 2023 )] and developmental genes correlated to dopamine such as manf ( Li et al, 2018 ; Qian et al, 2018 ; Li et al, 2020 ; Zhu et al, 2020 ; Tian et al, 2021 ; Hong et al, 2022 ; Heredia-García et al, 2023 ; Shi et al, 2023 ), otpa , otpb ( Wang et al, 2019 ), wnt1 ( Ho et al, 2013 ), wnt5b ( Ho et al, 2013 ), wnt10b ( Xu et al, 2022a ), wnt4a ( Xu et al, 2022a ), wnt3a , wnt5a ( Wang et al, 2019 ) can be analysed ( Supplementary Table S2 ). Treatment with lead in zebrafish larvae significantly reduced the number of dopaminergic neurons in the midbrain ( Jin et al, 2019b ).…”
Section: Neurotransmissionmentioning
confidence: 99%
“…Zebrafish, an ideal aquatic sentinel organism, has been widely used in the study of environmental toxicology and pharmacology due to biological advantages such as the small size, easy cultivation, and high homology with the human genome . As the most critical detoxification organ, the liver poses a vital significance in biological metabolism and removal of exogenous toxic substances .…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish, an ideal aquatic sentinel organism, has been widely used in the study of environmental toxicology and pharmacology due to biological advantages such as the small size, easy cultivation, and high homology with the human genome. 14 As the most critical detoxification organ, the liver poses a vital significance in biological metabolism and removal of exogenous toxic substances. 15 Zebrafish liver metabolism and immune response are very similar to those of mammals, and most researchers believe that zebrafish can be used as a model organism for the study of drug-induced liver injury.…”
Section: Introductionmentioning
confidence: 99%
“…The ubiquity of PFASs in the environment may threaten the health of aquatic organisms due to the strong bioenrichment and potential toxicity at environmental concentrations. Previous studies have confirmed that the immune system is a sensitive target to PFASs . Perfluorooctanesulfonate (PFOS) and its alternatives, chlorinated polyfluorinated ether sulfonate and sodium p-perfluorous nonenoxybenzene sulfonate, disrupted an antioxidant response and induced anti-inflammatory effects in exposed zebrafish larvae .…”
Section: Introductionmentioning
confidence: 99%